Computerized Cognitive Training in Amnestic Mild Cognitive Impairment: A Randomized Clinical Trial. (May 2022) - Duff, Kevin; Ying, Jian; Suhrie, Kayla R.; Dalley, Bonnie C.A.; Atkinson, Taylor J.; Porter, Sariah M.; Dixon, Ava M.; Hammers, Dustin B.; Wolinsky, Fredric D.
Objective: Computerized cognitive training has been successful in healthy older adults, but its efficacy has been mixed in patients with amnestic Mild Cognitive Impairment (MCI). Methods: In a randomized, placebo-controlled, double-blind, parallel clinical trial, we examined the short- and long-term efficacy of a brain-plasticity computerized cognitive training in 113 participants with amnestic MCI. Results: Immediately after 40-hours of training, participants in the active control group who played computer games performed better than those in the experimental group on the primary cognitive outcome (p = 0.02), which was an auditory memory/attention composite score. There were no group differences on 2 secondary outcomes (global cognitive composite and rating of daily functioning). After 1 year, there was no difference between the 2 groups on primary or secondary outcomes. No adverse events were noted. Conclusions: Although the experimental cognitive training program did not improve outcomes in those with MCI, the short-term effects of the control group should not be dismissed, which may alter treatment recommendations for these patients.